Surgical Management and Outcome of Adnexal Masses during Pregnancy: A 2 Year Retrospective Study - Nahar, Shamsun; Begum, Taslima; Nahar, Lutful; Siddique, Tanzeema; Rani, Chalontika; Raihan-ul-Kabir, Mohammad (Bangladesh Journal of Obstetrics & Gynaecology, 2010)
Objective: To demonstrate adnexal masses during pregnancy Materials and Methods: This retrospective hospital based study was carried out in the department of Obstetrics & Gynaecology of Sir Salimullah medical college & Mitford hospital, Dhaka, between June 2007 to June 2009. Results: Among 5320 live births fourteen pregnancies with adnexal masses were detected during the study period. The mean age group of the patients was 26.6 year (range 18-42 yrs), the mean gestational age at which adnexal masses were detected was 17 weeks (range 5-36 wks) and the mean gestational age at the time of surgery was 24 weeks (range 6-41wks). Conclusion: This study demonstrated a high rate of surgical intervention of adnexal masses during pregnancy. Most cases were benign in character and malignancy rate was very low. DOI: 10.3329/bjog.v23i2.4959 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(2) : 51-55